It started with a Vegas wedding - Gilmore, Jessica (Harlequin romance, 2023)
"Married in haste-- together forever? When a near accident in Vegas lands sensible Willow in the arms of her boss's son, gorgeous adrenaline addict and tycoon, Logan, she decides it's time to live a little. The result? One spontaneous Vegas-style wedding-- which was meant to be followed by a prompt annulment. Until Logan realizes the benefits of staying married for a year! He makes Willow a deal, but their extra time together only confirms that the attraction that started in Vegas is stronger than ever--"--